Mediation Satisfaction: The Role of Service Quality and Trust to Increasing Customer Loyalty in Bank Indutries - Subiyanto, Tri Bagus; Susbiyani, Arik; Martini, Ni Nyoman Putu; Qomariah, Nurul (Yayasan Sinergi Kawula Muda, 2025)
Competition in the banking sector is currently increasing. The banking industry is required to continuously improve services so that it has an impact on customer satisfaction and loyalty. The purpose of this study is to address the inconsistency of results by analyzing the influence of service quality and trust on customer satisfaction and loyalty at PT. BRI Finance Jember. The measuring instrument is a questionnaire with a population of 186 customers of PT. BRI Finance Jember who also served as the research sample. Structural Equation Modeling (SEM) with the help of the WarpPLS application is used in this study to test the hypothesis. Finally, the results of the study show that service quality has an impact on satisfaction. Trust has an impact on satisfaction and loyalty. Service quality has an impact on loyalty. Trust has an impact on loyalty. Satisfaction has an impact on loyalty. In addition, customer satisfaction acts as an intervening variable that strengthens the influence of service quality and trust on customer loyalty. These findings emphasize the importance of improving service quality and building trust as the main strategy in maintaining and increasing customer loyalty of PT. BRI Finance Jember. This research provides practical contributions to applied marketing management and designing service management policies to enhance customer satisfaction and loyalty in financial institutions in Southeast Asia.